Farmers and tumpang sari: Case study in Palintang Hamlet, Cipanjalu Village, Bandung, Indonesia - BUDIAWATI S. ISKANDAR; JOHAN ISKANDAR; HIKMAT A. WIBAWA; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2017)
Iskandar BS, Iskandar J, Wibawa HA, Partasasmita R. 2017. Farmers and tumpang sari: Case study in Palintang Hamlet, Cipanjalu Village, Bandung, Indonesia. Biodiversitas 18: 1135-1149. People of Palintang hamlet are recognized as one of the local communities reside in the high land of surrounding forest of Manglayang Mountain of West Java, Indonesia. Based on ecological or environmental history, they initially practiced the swidden farming in the natural forest of Manglayang, West Java. Moreover, some of them involved as labor in various activities of the culture systems during the Dutch colonial. After Indonesian independent, they have participated as laborer in the tumpang sari program of the Forest Service (Dinas Kehutanan) and the State Forestry Corporation (Perhutani). Nowadays,farmers of Palintang have intensively cultivated the pine forest for planting cash crops, including cabbage and potatoes. As a result, the farming practice in the forest has caused dilemma between providing cash income for local people and endangering the stability of environment for the near future. This paper presents the findings of research on the development of agroecosystems of a the Palintang people, in relation to social-ecological-changes, particularly the forest ecosystem changes. The method used in the study was combination of qualitative and quantitative. The result of study shows that the farmers of Palintang have continuously cultivated the forest for tumpang sari since the Dutch colonial period until now. Today, they have farmed the agroecosystems of the homegarden and mixed garden in their village land, and have intensively farmed vegetable garden in the forest of the Perhutani. Based on the inventory of crops in the mixed-garden (kebun or kebun campuran) and home garden, it was recoded 47 species and 42 species, respectively. The vegetables and fruits were predominantly found in both the mixed-garden and homegarden. The practice of the commercial vegetable crops as tumpang sari in the forests of the Perhutani has provided some benefits, including fulfilling cash income for farmer households, but some negative impacts on environment, such as pollution of pesticides have also occurred.